Estimating the extra disability expenditures for the design of inclusive social protection policies - Mont, Daniel (Frontiers in Rehabilitation Sciences, 2023)
For social protection policies to be inclusive they must address the extra costs that people with disabilities incur. Studies show that these costs are highly significant and if not taken into account the economic wellbeing of people with disabilities is underestimated. Additionally, disability costs vary significantly by the type and degree of disability. To align the structure of social protection programs with how costs are incurred to promote equal participation requires estimating those costs. The Goods and Services Required approach, it is argued, is better than the often used Standard of Living Approach, and has implications for policy design.